First-principles investigations to evaluate FeN2 as an electrocatalyst to improve the performance of Li–S batteries - Liyuan Jiang; Bingqian Wang; Yulin Zhou; Yan Jiang; Zongyao Zhang; Zhengdao Li; Xinxin Zhao; Jianbao Wu (Chemical Physics Impact)
The high energy density, low cost, and environmental sustainability of lithium-sulfur (Li–S) batteries render them highly promising as next-generation energy storage devices. Nevertheless, the commercial advancement of Li–S batteries faces obstacles, including the limited conductivity of sulfur, the shuttle effect of lithium polysulfides (LiPSs), and the suboptimal efficiency of the discharging/charging process. Based on the theoretical calculation of density functional, the potential application of an FeN2 single-layer as a catalyst in Li–S batteries to overcome the abovementioned problems is studied. The results show that the FeN2 single-layer molecules have a metal electron structure and soluble LiPSs can effectively coordinate and bond with FeN2. Improving the overall conductivity and anchoring effect of sulfur can effectively inhibit the shuttle effect caused by LiPSs. It is worth noting that the FeN2 single-molecule membrane has dual functions, and it has electrocatalytic activity on both the sulfur reduction reaction and the Li2S decomposition reaction, thus improving the conversion efficiency of the discharging and charging processes. These findings may provide a reference for the development of high-performance Li–S batteries.